The Indonesian Government’s Plan to Join BRICS Under the Leadership of Prabowo Subianto - ZUBAIDI, Abdul Khakim Mahfud (Journal of Political And Legal Sovereignty, 2024)
Purpose:The objective of this study is to examine Indonesia's steadfast commitment to an active and independent foreign policy in the context of its potential membership in BRICS. This research aims to assess how Indonesia balances its national interests while navigating complex global dynamics and pursuing strategic partnerships.Methodology:This study uses qualitative explanatory research with discourse analysis to explore narratives on Indonesia’s intention to join BRICS..Findings:Indonesia's intention to join BRICS reflects a strategic shift in its foreign policy, balancing economic opportunities and geopolitical challenges while testing its commitment to an independent and active stance. Indonesia’s potential membership in BRICS reflects its growing geopolitical influence and its desire to shape the future of global economic governance. This move is driven by the country’s ambition to diversify its international partnerships and enhance its bargaining power within major global institutions. By joining BRICS, Indonesia stands to gain greater access to emerging markets and increase its economic resilience on the world stage.Implication:Indonesia's potential membership in BRICS could serve as a gateway to unlock key economic opportunities, fostering enhanced trade, investment, and technological collaboration with emerging global powers. This strategic alignment may significantly bolster Indonesia's economic growth, providing access to new markets and reinforcing its role in the global economy.